2014
DOI: 10.3390/polym6122912
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Extrusions on the Properties of Montmorillonite Filled Polypropylene

Abstract: Nanocomposites have attracted a great deal of interest during recent years. Much research has been conducted towards the incorporation of clay particles in a polypropylene matrix. However, the effect of extrusion reprocessing on the material properties has not been studied in depth. In this study, composites of polypropylene (PP) reinforced with organic modified montmorillonite (MMT) (4 wt%) and coupling agent were subjected to 15 extrusion cycles. The materials were characterized by melt flow index (MFI), pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Because there was no comparable research found in the search of the literature, the findings of this study were compared with studies of WPCs reproduced by re-extrusion (Yarahmadi et al 2001;Delva et al 2014). In these studies, the properties of WPCs manufactured with the re-extrusion process were reduced with an increase in the number of re-extrusion cycles.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Because there was no comparable research found in the search of the literature, the findings of this study were compared with studies of WPCs reproduced by re-extrusion (Yarahmadi et al 2001;Delva et al 2014). In these studies, the properties of WPCs manufactured with the re-extrusion process were reduced with an increase in the number of re-extrusion cycles.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Recently, polymer nanocomposites, have received a great interest because they exhibit good mechanical, thermal and barrier properties [14,15]. Due to the growing market of nanocomposites, the scientific literature has currently studied the effect of reprocessing of the nanocomposites based on conventional polymers [13,[16][17][18][19]. Moreover, several studies investigated the effect of the reprocessing on the properties of neat biodegradable polymers, such as PLA [5,6,8,20].…”
Section: Introductionmentioning
confidence: 99%
“…After that, a longer mixing time has little effect on further exfoliation and intercalation of MMT layers. In previous work, the effect of extrusion cycles on PP/MMT under shear stress was studied. In that work, the XRD analyses also show the increasing mixing time could not led an exfoliated structure in the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile properties increase at first may be because the intercalated nanostructures can be obtained even when the mixing time is 1 min, which is determined by XRD analyses. In previous work, it is shown that the longer mixing time decreases tensile properties. Delva et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation